2017
DOI: 10.1080/08820538.2017.1395893
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Recurrent Retinal Detachment Surgery following Pars Plana Vitrectomy for Rhegmatogenous Retinal Detachment

Abstract: PVR ≥ Grade C and multiple resurgeries are associated with higher incidence of anatomical failure in recurrent RD surgery. Multiple breaks are associated with a poorer visual outcome, whereas a better baseline visual acuity and delayed recurrence of RD after primary repair are associated with a better visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…This inconsistency may be related to the frequency of follow-up visits. Overall, we found that the rate of total final success was 97.6%; these findings were comparable to those reported by previous studies [10,11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This inconsistency may be related to the frequency of follow-up visits. Overall, we found that the rate of total final success was 97.6%; these findings were comparable to those reported by previous studies [10,11].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that a wide variety of risk factors are associated with the recurrence of RD after RRD repair, including proliferative vitreoretinopathy (PVR) [12], inferior breaks [3], the duration of preoperative symptoms until surgery [13], lens status [14], vitreous hemorrhage [15], undetectable retinal tear [16], the extent of detachment [5], high myopia [17] and hypotonia [18], and the presence of multiple breaks [10]. Unlike these previous studies, our present study failed to identify significant differences between the groups of patients with recurrent and reattached RD with regards to age, gender, lens status, the number of breaks, detachment duration, the extent of the retinal detachment, high myopia, macula status, PVD, giant retinal tears, choroidal detachment, the use of perfluorocarbon liquid, retinectomy, and combined cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the studies quote PVR ≥ Grade C, anterior and inferior PVR to be associated with a higher risk re-RD. [ 6 7 8 9 10 11 12 13 14 15 16 17 19 20 21 22 26 ] It was previously reported that 86% of eyes with re-RD after vitrectomy have a component of anterior PVR[ 27 ] and eyes with anterior PVR have poorer surgical prognosis than those with posterior PVR. [ 28 ]…”
Section: Risk Factors Relating To Redetachmentmentioning
confidence: 99%
“…Surgical causes include multiple surgeries,[ 2 11 18 20 ] incomplete removal of the vitreous base and shaving,[ 19 20 ] retinectomies, and relaxing retinotomies. [ 33 ]…”
Section: Risk Factors Relating To Redetachmentmentioning
confidence: 99%
See 1 more Smart Citation